The Role of Routine Biopsy of the Lacrimal Sac During Dacryocystorhinostomy Surgery. (2nd November 2015) - Nash, Mitchell; Skippen, Brent; Gal, Andrew; Benger, Ross
Abstract: Purpose : To assess the role of routine histopathological evaluation of the lacrimal sac wall when performing dacryocystorhinostomy (DCR) surgery. Methods: A retrospective review was conducted of the histology findings in lacrimal sac biopsies, taken routinely, in an external-approach DCR series. This is a single surgeon (RB), single pathologist (AG) consecutive series. The histopathology reports were reviewed and collated. Each patient's medical history and risk factors for malignancy were recorded. The surgeon documented any abnormal lacrimal sac appearance at the time of surgery. Results : No patient in this series of 245, in whom 254 histology specimens were taken, recorded a significant pathological result that was not anticipated from pre-operative assessment, or from the appearance of the lacrimal sac intra-operatively. Conclusion : The reported recommendation for routine histopathological evaluation of the lacrimal sac wall when performing DCR surgery is not supported by this consecutive series. The authors recommend histopathological evaluation only in the setting of pre-existing clinical suspicion of malignancy, or an abnormal intra-operative appearance of the lacrimal sac.